Türkiye Burslar? as the Soft Power in the Reflection of Bilateral Relations between Türkiye and Indonesia - Muhammad Shalahuddin Al Ayyubi (Journal of Social Science, 2024)
Türkiye Burslar? is a scholarship program for international students, but who would have thought that the existence of this scholarship was in line with Turkey's public diplomacy mission and thus became the country's soft power? Indonesia, as a friendly country, is Turkey's main target in expanding its reputation and cultural promotion mission through Türkiye Burslar?, as evidenced by the government's policy in 2020 which plans to increase the quota for students from Indonesia. With its historical ties, similarities in religious identity, and cultural harmony, Turkey is certainly an alternative for Indonesian students to experience the experience of studying abroad. On the other hand, Indonesia, with its large population and GDP, is certainly Turkey's target in spreading its cultural values to create many agents who can fulfill national interests comprehensively from many sectors. This research seeks to analyze the influence and opportunities of the Türkiye Burslar? scholarship on Turkey's diplomatic relations with Indonesia in detail. The methodology used in this research is qualitative with references in the form of books, reports, and relevant journal articles according to the topic of Türkiye Burslar?'s role as Turkey's soft power and its relationship with Indonesia.